2010
DOI: 10.1104/pp.110.160275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Putative Stage-Specific Grapevine Berry Biomarkers and Omics Data Integration into Networks      

Abstract: The analysis of grapevine (Vitis vinifera) berries at the transcriptomic, proteomic, and metabolomic levels can provide great insight into the molecular events underlying berry development and postharvest drying (withering). However, the large and very different data sets produced by such investigations are difficult to integrate. Here, we report the identification of putative stage-specific biomarkers for berry development and withering and, to our knowledge, the first integrated systems-level study of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 102 publications
11
135
0
Order By: Relevance
“…Microarray analysis revealed that samples with unique characteristics (such as pollen grains and leaves undergoing senescence) were clearly distinguishable at the transcriptomic level from all other samples, which grouped more according to their maturity and developmental stage than their organ or tissue identity, as also supported by the in silico analysis of RNA-seq data. Previous studies have focused mostly on berry development and ripening (Zamboni et al, 2010;Zenoni et al, 2010;Tornielli et al, 2012), but our transcriptomic atlas presents a comprehensive grapevine transcriptome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Microarray analysis revealed that samples with unique characteristics (such as pollen grains and leaves undergoing senescence) were clearly distinguishable at the transcriptomic level from all other samples, which grouped more according to their maturity and developmental stage than their organ or tissue identity, as also supported by the in silico analysis of RNA-seq data. Previous studies have focused mostly on berry development and ripening (Zamboni et al, 2010;Zenoni et al, 2010;Tornielli et al, 2012), but our transcriptomic atlas presents a comprehensive grapevine transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…previously been identified as a positive biomarker of withering in Corvina berries (Zamboni et al, 2010). Several transcripts encoding stress response, ethylene response, and protein recycling functions were strongly represented in mature/woody samples, along with a population of (predominantly zinc finger) transcription factors, suggesting that significant transcriptional reprogramming is required for the transition to the mature phase.…”
Section: Molecular Biomarkersmentioning
confidence: 98%
See 2 more Smart Citations
“…Insights into the genetic mechanisms that mediate fruit ripening-related processes, such as cell wall metabolism, pigment synthesis, and sugar metabolism, have resulted from studies that collectively span a wide range of plant species and indicate that they are broadly conserved (Seymour et al, 2008;Moing et al, 2011;Zhang et al, 2011). However, certain speciesspecific differences exist in the dynamics of other metabolite pools across ripening, with, for example, grape (Vitis vinifera), strawberry (Fragaria 3 ananassa), prune (Prunus domestica), and pepper (Capsicum annuum) displaying slightly different metabolic programs from tomato (Solanum lycopersicum; Zamboni et al, 2010;Lombardo et al, 2011;Osorio et al, 2011Osorio et al, , 2012Zhang et al, 2011). This fact notwithstanding, tomato has become the primary experimental model in which to study the development and ripening of fleshy fruits (Giovannoni, 2004;Fernandez et al, 2009).…”
mentioning
confidence: 99%